Pelatihan Prosedur Pengemasan dan Menejemen Penyimpan Complete Feed Block di Desa Lembengan - Muhammad Faris Nailus Surur; Yopy Arya Dwi Nanda; Diva Alfith Erlingga; Muhammad Arga Hita (Jurnal Pengabdian Kepada Masyarakat, 2026)
Community service in the beef cattle sector in Lembengan Village has the potential for a very high population. However, livestock farmers in Lembengan Village face challenges related to understanding the packaging procedures and storage management of complete feed blocks, which can impact feed availability. The community service methods used included focus group discussions, outreach, and direct demonstrations related to the packaging procedures and storage management of complete feed blocks. This community service activity successfully improved livestock farmers' understanding and skills in the packaging and storage management processes of livestock feed to maintain availability and minimize feed waste. The livestock feed packaging procedure is carried out under anaerobic conditions and is stored on racks. The feed storage management principle uses the principle of first in, first out and the principle of safety stock inventory.